Ward milieu and the management of in-patient violence: use of seclusion and other restrictive practices - Davoren, Mary (Seminars in forensic psychiatry, 2024)
Increasingly, secure forensic mental health services must balance reducing restrictive practices on one hand with keeping a violence free environment on the other. Nursing staff and other hospital staff have the right to work in a safe environment. They should not be subject to intimidation and assaults in the work setting. Patients have the right to care in a safe environment and they need to have confidence that staff members can keep them safe during their in-patient stay. Minimising in-patient violence and minimising past violence for forensic patients is undermining an area of significant treatment need and may seriously limit the patient’s chance of a future successful discharge in the community. We posit in this chapter that active and careful management of ward milieu and dynamics, and active treatment of psychotic and other symptoms, together with proportionate use only of restrictive practice and thorough evaluation of any and all restrictive practice is the most effective way of managing a forensic in-patient setting to effectively reduce and prevent incidents of violence.